2018
DOI: 10.1111/eva.12606
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping‐by‐sequencing of genome‐wide microsatellite loci reveals fine‐scale harvest composition in a coastal Atlantic salmon fishery

Abstract: Individual assignment and genetic mixture analysis are commonly utilized in contemporary wildlife and fisheries management. Although microsatellite loci provide unparalleled numbers of alleles per locus, their use in assignment applications is increasingly limited. However, next‐generation sequencing, in conjunction with novel bioinformatic tools, allows large numbers of microsatellite loci to be simultaneously genotyped, presenting new opportunities for individual assignment and genetic mixture analysis. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 42 publications
7
97
0
Order By: Relevance
“…They reviewed different NGS methods of SSR identification and primer development and discussed the pros and cons of using genotyping‐by‐sequencing (GBS) or restriction site‐associated DNA sequencing (RAD‐seq) in comparison to SSRs. That SSRs are not dead is reflected in the development of new analytical tools, for example, for the automatic inference of SSR genotypes (Zhan et al, ), and in a variety of publications that employed NGS for obtaining SSR sequence data directly from PCR amplicons (Bradbury et al, ; De Barba et al, ; Vartia et al, ). While these studies used animals as study systems, similar approaches have not yet been applied to plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reviewed different NGS methods of SSR identification and primer development and discussed the pros and cons of using genotyping‐by‐sequencing (GBS) or restriction site‐associated DNA sequencing (RAD‐seq) in comparison to SSRs. That SSRs are not dead is reflected in the development of new analytical tools, for example, for the automatic inference of SSR genotypes (Zhan et al, ), and in a variety of publications that employed NGS for obtaining SSR sequence data directly from PCR amplicons (Bradbury et al, ; De Barba et al, ; Vartia et al, ). While these studies used animals as study systems, similar approaches have not yet been applied to plants.…”
Section: Discussionmentioning
confidence: 99%
“…In order to tackle the homoplasy problem and assess FR variation, some authors combined cloning or single‐strand conformation polymorphism and sequencing (e.g., Germain‐Aubrey et al, ; Lia, Bracco, Gottlieb, Poggio, & Confalonieri, ; Ortí, Pearse, & Avise, ; Šarhanová et al, ), but these methods are costly, time‐consuming, and not easily applicable for polyploids. There are first forays among animals (Bradbury et al, ; De Barba et al, ; Vartia et al, ), but comparisons between traditionally scored fragment length data and the information obtained from sequencing are still missing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When microsatellites are the preferred marker due to high polymorphism or existing datasets, amplicon sequencing methods can also be applied to transition from capillary sequencing to a next‐generation sequencing based approach (Zhan et al, ). Bradbury et al () highlight this approach by identifying 101 microsatellite loci from the available Atlantic salmon genome and genotyping 1,558 individuals via amplicon sequencing. The results of this study identified previously undescribed fine‐scale population structure in Atlantic salmon.…”
Section: Amplicon Sequencing and Sequence Capture Facilitate The Tranmentioning
confidence: 99%
“…) Bradbury et al (2018). highlight this approach by identifying 101 microsatellite loci from the available Atlantic salmon genome and genotyping 1,558 individuals via amplicon sequencing.…”
mentioning
confidence: 99%